Differential Metabolic Pathway Analysis of the Proteomes of Leishmania donovani and Leptomonas seymouri. Issue 5 (25th March 2018) - Singh, Neeloo; Goel, Renu; Jain, Ekta
Abstract : Purpose: Although in trypanosomatids, monoxeny ( Leptomonas) is ancestral to dixeny ( Leishmania ), however clinical cases of visceral leishmanisis with Leptomonas co‐infection are increasingly being reported from India. Using a proteogenomic approach, a detailed proteome analysis of these two kinetoplastid parasites viz., Leishmania and its sister Leptomonas, to catalog the key proteins associated with and therefore possibly responsible for phenotype changes in Leptomonas evolution and domestication as co‐infection with Leishmania is carried out. Experimental design: LC–MS/MS is utilized for this proteomic purpose. One Leishmania donovani WHO reference strain and two Leptomonas seymouri isolates, which are originally isolated from clinical cases of kala azar patients with different inherent drug sensitivity viz., responsive and unresponsive, are used in this study. Results: A network analysis, leveraging protein–protein interaction data helped to find the roles of the proteins in carbon metabolism and biosynthesis of secondary metabolites which is seen to be altered under stress conditions like drug resistance. Conclusions and Clinical relevance: The information provided about the metabolic pathways modulated when contrasting these two phenotypes may lead to the development of new strategies to block parasite differentiation within the host and to also circumvent the problem of drug resistance. This proteomic study also offers new grounds for the investigation of novel hypothetical proteins potentially playing a role in evolutionary biology the knowledge of which is essential for treatment of patients co‐infected with these two kinetoplastid parasites.